Rutas de muerte en la narrativa de Claudia Hernández - Gairaud Ruiz, Hilda (2015)
This article explores the aesthetics presented in some narratives written by the Salvadorian author Claudia Hernández within the frame of the postwar literature. Images of violence and death and their printings in bodies and psyques dominate the content of her fiction and they illustrate the realities that Salvadorians faced in the context of the civil war and postwar periods. Plot and characters embody how violence in all its expressions has affected the process of construction of subjectivity and has become a legacy of their history.